„Upojeni wolnością”. Historia i idee Praskiej Wiosny jako próba wdrożenia socjalizmu z ludzką twarzą - Dubel, Lech; Niemczyk, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The events in Czechoslovakia referred to as the Prague Spring were not about overthrowing the system but were agenuine attempt to introduce a“socialism with ahuman face”. The aim of the article is to examine the history and ideas especially the idea of freedom that constituted the foundations of the Prague Spring. The authors do this, taking into account several research perspectives relating to doctrine, political-legal solutions and civic engagement. In addition, they analyse the ideological documents behind these events, i.e. the programme of the Communist Party of Czechoslovakia, the Two Thousand Words manifesto and documents of the 14th Congress of the Communist Party of Czechoslovakia.
Keywords: wolność; socjalizm z nieludzką twarzą; rewizjonizm; Czechosłowacja; Praska Wiosna